Innovation of Enterprise Management in the Era of Artificial Intelligence - Chen, Keyu (International Journal of Global Economics and Management, 2024)
As a product of social development and technological innovation, Artificial Intelligence has become the driving force of technological innovation and industrial transformation. It profoundly impacts the world economy, social progress as well as people’s lives. Artificial Intelligence’s commercial applications innovate enterprises’ internal operations and production processes, bringing both challenges and opportunities for management. This article analyses innovation in modern enterprise management with specific applications of AI to management theories. Some suggestions are also made for enhancing the application level of Artificial Intelligence in enterprise management.